Comparison of Photographic Screening Methods for Diabetic Retinopathy – A Meta-analysis. (4th May 2023) - Yan, William; McGuinness, Myra; Chakrabarti, Rahul; Fotis, Kathy; Finger, Robert P.
ABSTRACT: Introduction: Diabetic Retinopathy (DR) is a leading cause of irreversible visual impairment and blindness in both developed and developing countries. Although the merits of DR screening are well recognized, significant variations in screening practices including imaging modality still exists. Purpose: To evaluate and compare the sensitivity and specificity of mydriatic and non-mydriatic photographic screening methods using 7-Field fundus photography or dilated fundus examination (DFE) by an ophthalmologist as reference standard. Methods: A systematic review using PRISMA Guidelines was conducted by online search of MEDLINE, Web of Science, and other repositories of all available studies from 1990 until 2019. A total of 62 studies were included in the meta-analysis from a total of 406 suitable abstracts screened and 95 articles reviewed in full. Data were collected using a standardized extraction form independently, with all authors masked to others' search results. Results: For the detection of any DR (ADR), sensitivity ranged from 81% with single field to a maximum of 99% for 4–7 fields and wide-angle images. For detection of referable DR (RDR) sensitivity ranged from 76% for single field to 93% for wide-angle photography. Specificity was lowest at 91% for wide-angle images and greatest at 99% for three field photography. Study heterogeneity was noted to be significant, which was partly attributed to the range of DR classification between studies. Conclusions: The sensitivity and specificity of DR screening are positively associated with number of photographic fields. Pooled estimates suggest non-mydriatic two-field photography may be sufficient for screening detection of ADR and RDR.